2014
DOI: 10.1021/jp507581c
|View full text |Cite
|
Sign up to set email alerts
|

Magnetical and Optical Properties of Nanodiamonds Can Be Tuned by Particles Surface Chemistry: Theoretical and Experimental Study

Abstract: In this paper, new steps toward a better understanding and utilization of high-pressure high-temperature nanodiamonds (NDs) containing nitrogen-vacancy (NV) centers have been taken. NV − -related long-term luminescence of oxygenated particles increased in comparison to plasma hydrogenated NDs' NV − luminescence. The optically detected NV − electron spin resonance process can be also significantly affected by ND termination. For Hterminated ND particles the NV − to NV 0 conversion energy is lower than the NV − … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…CLSM was used to confirm the intracellular uptake of NDs with or without LF. Previous study showed that ND particles can be internalized through the cell membrane and accumulate in the cytoplasm [31]. Consistent with the previous results, after 4 h incubation, FITC-conjugated NDs were observed around the cytoplasm and nuclei of cells ( Figure 4B).…”
Section: In Vitro Lf Releasesupporting
confidence: 92%
“…CLSM was used to confirm the intracellular uptake of NDs with or without LF. Previous study showed that ND particles can be internalized through the cell membrane and accumulate in the cytoplasm [31]. Consistent with the previous results, after 4 h incubation, FITC-conjugated NDs were observed around the cytoplasm and nuclei of cells ( Figure 4B).…”
Section: In Vitro Lf Releasesupporting
confidence: 92%
“…Over the past decades, nanomaterials have attracted great attention with C-BNM being among the most studied ones. Their extraordinary physicochemical properties, namely, tuneable electronic (e.g., band gap) and electrical properties (e.g., conductivity), thermal and chemical stability, and large surface area, make C-BNM appropriate candidates for a wide range of high-tech applications, as well as for biomedical applications [1][2][3][4][5][6]. Chemical industry is capable of producing C-BNM in large quantities and, therefore, their impact on the environment is inevitable.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles (NPs) provide extraordinary opportunities as drug nanocarriers [17][18][19], due to their prolonged circulation time and both passive and active targeting abilities towards cancerous tissues/cells. The conjugation of peptides to NPs represents an effective approach to addressing the intrinsic drawbacks of the peptides, allowing the access to a variety of biomedical uses [20,21].…”
Section: Introductionmentioning
confidence: 99%